Explaining the Impact of Legal Access to Cannabis on Attitudes toward Users. (14th April 2023) - Queirolo, Rosario; Repetto, Lorena; Sotto, Belén; Álvarez, Eliana
Abstract: Laws and public policies can change social norms by signaling which behaviors are legal or illegal. Recent cannabis legalization policies might have this effect. Does cannabis legalization increase social acceptance toward its users? This article focuses on understanding the impact of Uruguayan cannabis legalization on attitudes toward cannabis users by taking advantage of having legal and illegal mechanisms for getting cannabis under the same national context. To do so, we conducted a conjoint experiment in a national face-to-face survey ( N = 2, 181). Participants were presented with two different profiles of potential neighbors and asked to choose one. These profiles randomized attributes such as being a registered user, mechanism of cannabis acquisition, frequency of cannabis use, as well as sociodemographic characteristics. Participants rated each profile from 1 to 7 based on how much they would like to have them as neighbors. Subsequently, we estimated the average marginal component effect as the critical causal quantity of interest. Results reveal that users who access cannabis through a legal mechanism are more preferred as neighbors than those who do not. Thus, the evidence presented in this article indicates that regulation, by proving legal access, increases the social acceptance of cannabis users.